A Comparative Review of Equine SIRS, Sepsis, and Neutrophils - Sheats, M. Katie (Frontiers in Veterinary Science, 2019)
The most recent definition of sepsis in human medicine can be summarized as organ dysfunction caused by a dysregulated host response to infection. In equine medicine, although no consensus definition is available, sepsis is commonly described as a dysregulated host systemic inflammatory response to infection. Defense against host infection is the primary role of innate immune cells known as neutrophils. Neutrophils also contribute to host injury during sepsis, making them important potential targets for sepsis prevention, diagnosis and treatment. This review will discuss history and updates regarding sepsis and the systemic inflammatory response syndrome (SIRS), as well evidence for the role neutrophils play in sepsis. Future identification of clinically relevant sepsis diagnosis and therapy depends on a more thorough understanding of disease pathogenesis across species. To gain this understanding, there is a critical need for research that utilizes a clearly defined, and consistently applied, classification system for patients diagnosed with, and at risk of developing, sepsis.